Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Cerveau, sexe et pouvoir - Vidal, Catherine; Benoit-Browaeys, Dorothée. (Regards, 2005)
À la lumière des connaissances actuelles en neurosciences, on serait tenté de croire que les vieux préjugés sur les différences biologiques entre les hommes et les femmes ont été balayés. Ce n'est manifestement pas le cas : médias et ouvrages de vulgarisation prétendent que les femmes sont " naturellement " bavardes et incapables de lire une carte routière, tandis que les hommes sont nés bons en maths et compétitifs. Ces discours laissent croire que nos aptitudes, nos émotions, nos valeurs sont tablées dans des structures mentales immuables depuis les temps préhistoriques. Cet ouvrage, qui s'adresse à un large public, replace le débat autour de la différence des sexes sur un terrain scientifique rigoureux, au-delà des idées reçues. L'enjeu est de comprendre le rôle de la biologie, mais aussi l'influence de l'environnement social et culturel dans la construction de nos identités d'hommes et de femmes. Notre destin n'est pas inscrit dans notre cerveau! [Source : d'après la 4e de couv.].
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; discours dominant; inégalités; neuropsychologie; neurosciences; premier cycle; psy4910; psychologie; périodes historiques; sciences; sciences humaines; sexe/genre; sexisme; systèmes d'oppressions; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques